Model Kepemimpinan Efektif dan Produktivitas Pegawai pada Birokrasi Teknis: Studi Empiris di Dinas Bina Marga dan Penataan Ruang Jawa Barat - Abdul Patah; Hari Imbrani; Wati Rahayu (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2026)
This study examines how effective leadership impacts increased employee productivity within the technical bureaucracy within the West Java Provincial Highways and Spatial Planning Agency. Effective leadership is understood as a leader's ability to provide direction, motivation, and empowerment to employees in order to optimally achieve organizational goals. The research method uses a quantitative approach through a survey of 50 ASN respondents working at the UPTD for Road Management Region III. The regression results show R = 0.58 and R² = 0.336, while the PLS analysis displays a path coefficient of β = 0.58 and a t-test of 5.91 (p < 0.05). These findings confirm that exemplary leadership, transparent communication, and employee empowerment can increase work productivity in the technical bureaucracy. This study also found that leadership that directly exemplifies behavior and decision-making can influence employee productivity levels in the public sector. Inspirational and participatory leadership, which involves employees in important decisions, shows a significant influence on increasing work morale and innovation. For example, employees who feel encouraged by their leaders to contribute more tend to show initiative in their tasks and take more responsibility for the work assigned.